Population characteristics and habitat suitability of Khao Yai National Park, Thailand for Asian elephant and five ungulate species - MANANYA PLA-ARD; NORASET KHIOESREE; BENCHARONG SUNGKALAK; ANUTTARA NATHALANG; WARISARA THOMAS; SUWIMON UTHAIRATSAMEE; PAANWARIS PAANSRI; YUWALAK CHANACHAI; RONGLARP SUKMASUANG (Society for Indonesian Biodiversity, 2022)
Abstract. Pla-ard M, Khioesree N, Sungkalak B, Nathalang A, Thomas W, Uthairatsamee S, Paansri P, Chanachai Y, Sukmasuang R. 2021. Population characteristics and habitat suitability of Khao Yai National Park, Thailand for Asian elephant and five ungulate species. Biodiversitas 23: 231-243. This study of population characteristics and habitat suitability of Asian elephant (Elephas maximus Linnaeus, 1758) and five ungulate species was conducted between October 2017 and July 2020 in Khao Yai National Park (KYNP) using camera traps. One hundred and twenty-two camera trap locations were set up for a total of 4,139 trap nights and 5,461 independent encounters were identified. The target species of Asian elephant, gaur, sambar deer, wild boar, northern red muntjac and lesser oriental chevrotain were recorded. The results show the occupancy of Asian elephant was 1.21 individuals/km2 within the study area. The probability occupancy of the Asian elephant was 70% (SE=0.06). In comparison, gaur had a probability occupancy of 57% (SE=0.07), whereas sambar deer was 79% (SE=0.04), followed by wild boar 77% (SE=0.05), northern red muntjac 77% (SE=0.05) and lesser oriental chevrotain occupancy 63% (SE=0.07). The age structure of Asian elephant between calf, juvenile, sub-adult and adult was 1: 2.1: 1.2: 3.16, and the ratio between adult males and females was 1: 1.72. The results show that roads and salt lick sites were the essential factors affecting the chance of Asian elephants and ungulate species in the area. The habitat suitability for Asian elephant was 331 km2, while those for gaur, sambar deer, wild boar, northern red muntjac and lesser oriental chevrotain were 287.73 km2, 249.97 km2, 540.40 km2, 451.34 km2 and 434.30 km2, respectively. Recommendations for further management involve concentration on the suitable area resulting from this study. Concerning the suitability habitat, it was found that the park boundary was most suited. Therefore, habitat improvements for all large herbivorous mammal species should improve the areas within the national park and especially address the central area, with an emphasis on creating salt lick sites, in addition to grassland and water sources that must be quality and sufficient, the most important habitat factor for these species.